Peter Rabbit [videorecording (Blu-Ray + DVD)] - Gluck, Will; Lieber, Rob, 1976-; Bazzi, Fayssal; Byrne, Rose; Gleeson, Domhnall, 1983-; Neill, Sam; Ridley, Daisy, 1992- (Sony Pictures Home Entertainment, 2018)
Feature adaptation of Beatrix Potter's classic tale of a rebellious rabbit trying to sneak into a farmer's vegetable garden.